PEMBARUAN PENGELOLAAN KEUANGAN DESA MELALUI SDG’S DESA: DAPATKAH MENUTUP KETERBATASAN SISTEM KEUANGAN DESA? (STUDI PADA DESA DI KABUPATEN LOMBOK BARAT) - Sapto Hendri BS.; Wirawan Suhaedi; Intan Rakhmawati (Jurnal Aplikasi Akuntansi, 2022)
The village government is a work unit under four ministries. In the financial aspect, the village government is regulated by the Ministry of Home Affairs, Ministry of Finance, Ministry of Villages, Development of Disadvantaged Regions, and Transmigration. Meanwhile, in the aspect of transparency, village government is regulated by the Ministry of Information and Communication, as well as Villages, Development of Disadvantaged Regions, and Transmigration. The complexity of regulations from four ministries is added to the direction of village financial management performance using the SDG's (Sustainable Development Goals) concept, with 247 indicators in it, since 2021. This study aims to analyze the perception and understanding of village financial management officers and village assistants, with the new village financial system pattern, which is set by the Village, Development of Disadvantaged Regions, and Transmigration and the Ministry of Home Affairs. The target village is a developing village. Based on the type of research, this research has the theme of public accounting that leads to behavior and systems, with an exploratory interpretive descriptive type of research. As a result, there has been no integration of SDG's data collection from Ministries, agencies, and agencies related to SDG's data.